Income Analysis of Farmers Using Rice Transplanter Technology as an Innovation for Rice Planting to Supporting Sustainabilty Agriculture - Dina Aprianty Azis; Irmayani Irmayani; Muh Ikbal Putera Bakhtiar (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
Sidrap Regency is one of the food barns in South Sulawesi, which can supply the rice needs of the surrounding area. Thus, efforts are made to introduce technology and innovation in their agricultural cultivation business so that farmers can increase their income with their legalized rice cultivation business. The puIDRose of this study was to find out how much rice farming income was earned by farmers when introducing Rica transplanter technology in their farming. This research is a quantitative descriptive study with variables that determine income analysis in the form of total production and costs used. The results showed that the rice planter system with the Rice Transplanter machine is still not widely used by farmers because the application of technology in the agricultural sector is also not something easy, one of which is because farmers' habits and understanding of technology are still lacking, besides that agricultural activities are also a source of livelihood for farmers so that farmers do not readily change old habits that have been adopted so far. The results showed that the income earned by farmers while adopting the Rice Transplanter technology was IDR 37,295,100, which indicates that there was no significant increase in Rice Transplanter innovation. This is because some farmers do not understand more deeply about the maximum use of this technology, so they still mix conventional uses.